(untitled) (Fiep Bulletin - online, 2014)
This study had as objective analyzes the relationship that apprentices of general gymnastic establish with the health. Characterized as of the descriptive type. The measure instrument was a questionnaire. It is concluded that the concept of health just includes some of their determinants and the general gymnastic can participate in the process of promotion of health.